Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Pemahaman Konsep dan Penalaran Geometris Siswa - Siti Mudhiah; Ali Shodikin (Jurnal Elemen, 2019)
Student learning achievement in Indonesia is low, this is because there are still many students who experience difficulties in learning geometry. To overcome these problems a way is needed so that students can understand concepts meaningfully and have good geometrical reasoning. This is certainly related to the appropriate learning model to be used in the learning process. One model of learning that can be used is a problem-based learning model. The purpose of this study is to describe the ability to understand the concepts and geometric reasoning of students who acquired a problem-based learning model compared with students who received conventional learning on quadrilateral material in class VII MTs. Tanwiriyah Kalisari. The research method used is quantitative with quasi-experimental research design. The results of the study showed that the ability to understand the concept of students who obtained a problem-based learning model was better than the ability to understand the concept of students who obtained conventional learning models. as well as the geometric reasoning abilities of students who acquired a better masculine learning model compared to the geometric reasoning abilities of students who acquired the conventional learning model.